Optimizing Seating in the Intensive Care Unit for Patients With Impaired Mobility - Williams, Teresa; Leslie, Gavin; Bingham, R.; Brearley, L. (American Association of Critical Care Nurses, 2011)
Background: Having intensive care patients sit out of be improves their respiration and psyche and reduces complications of immobilization.Objectives: To compare seating interface pressures to determine a preferred seating surface for patients sitting oout of bed. Method: The study was conducted in 2 phases among intensive care patients with impaired mobility who could sit out of bed. Pressure mapping was used to test seating surfaces in a non-randomized crossover design. In phase 1, three surfaces were compared: (1) regular chair (TotaLift-II), (2) regular chair with gel overlay, and (3) alternative chair (Hausted APC). A new surface, informed from phase 1, was designed and compared with the regular chair surface in phase 2. The number of cells recording pressures of 200 mm Hg or higher (excessive pressure) for 30 minutes was compared between surfaces.Results: In phase 1, the alternative chair had fewer excessive pressures than did the regular chair in 67% of seating episodes among 18 patients (P<.001), but the alternative chair lacked practical utility. In phase 2, the new seating surface was compared with the regular surface using the regular chair frame for 20 patients. Among patients with excessive pressures, most (93%) had fewer excessive pressures recorded on the new than on the regular surface (P<.001). Conclusion: Results from this study provided important data for development of a new seating surface for intensive care patients sitting out of bed. The new surface promotes patients' comfort and probably reduces risk of pressure ulcers.